Sufficiency of Kalman's rank condition for the approximate boundary controllability on a spherical domain. (5th July 2021) - Zu, Chengxia; Li, Tatsien; Rao, Bopeng
Abstract : We establish the sufficiency of Kalman's rank condition on the approximate boundary controllability at finite time for diagonalizable systems on a spherical domain in higher dimensional case.